Neomodernisme Islam dalam Perspektif Fazlur Rahman - Hana Widayani (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2020)
According to observers of Islamic thought, Fazlur Rahman is a figure whose thoughts are categorized as neomodernism, a pattern of thought that combines modern and traditional thought. Modernism, according to this pattern, is not something to be rejected, but modernism does not mean that the nature of traditionalism must be set aside. This is certainly in line with the Islamic thought of Fazlur Rahman who is always in developing his thoughts to see the development of past thoughts. In some cases, even the two realms of thought (modernism and traditionalism) can go hand in hand. If people follow Fazlur Rahman's way of thinking in all his works according to Syafi'i Ma'arif, people will know that he is very interested in developing the awareness of Muslims about their historical responsibilities with a solid moral foundation. This foundation can only be created if the Koran as a source of perfect moral teaching is understood in full and unified. This true and complete understanding must be done through a methodology that can be accounted for in a religious and scientific manner. According to Rahman, without an accurate and correct methodology, an understanding of the content of the Qur'an may be misleading, especially when approached partially and separately.